2014
DOI: 10.1113/expphysiol.2013.076828
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediated diaphragm fatigue in a rat model of chronic intermittent hypoxia

Abstract: New Findings r What is the central question of this study?The effects of chronic intermittent hypoxia (CIH) on respiratory muscles are relatively underexplored. It is speculated that muscle dysfunction and other key morbidities associated with sleep apnoea are the result of CIH-induced oxidative stress. We sought to investigate the putative role of CIH-induced reactive oxygen species in the development of respiratory muscle dysfunction. r What is the main finding and its importance?The CIH-induced diaphragm mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 74 publications
9
68
0
Order By: Relevance
“…However, LTF-driven increases in ventilatory output are mediated in part by slight increases in oxidative stress and other signaling pathways (106 -108) and have been successfully harnessed as an approach aiming to rehabilitate patients after spinal cord injury (69,128,129). However, LTF-generating paradigms could lead to long-term muscle fatigue with remodeling of the upper airway muscles and diaphragm and ultimately deleterious effects on motor control (53, [175][176][177][178]. This dysfunction emerges as highly dependent on factors such as age (177) or sex (176).…”
Section: Whenmentioning
confidence: 99%
“…However, LTF-driven increases in ventilatory output are mediated in part by slight increases in oxidative stress and other signaling pathways (106 -108) and have been successfully harnessed as an approach aiming to rehabilitate patients after spinal cord injury (69,128,129). However, LTF-generating paradigms could lead to long-term muscle fatigue with remodeling of the upper airway muscles and diaphragm and ultimately deleterious effects on motor control (53, [175][176][177][178]. This dysfunction emerges as highly dependent on factors such as age (177) or sex (176).…”
Section: Whenmentioning
confidence: 99%
“…However, a subsequent study convincingly demonstrated that IH exposure of just 4 days in mice was sufficient to cause autophagy-associated atrophy of diaphragm, leading to weakness, which recovered in normoxia 52. Interestingly, Shortt et al50 demon strated that rat diaphragm force and fatigue are affected in a manner dependent on the duration and intensity of the CIH exposure. Weakness and increased fatigue were observed following a 2-week exposure to IH (fractional of inspired oxygen concentration [FiO 2 ]=5% at nadir; 20 cycles per hour; 8 hours per day), with no muscle atrophy, but an increase in the relative area of MHC type 2B fast fibers and concomitant increase in the relative area of sarcoplasmic reticulum calcium ATPase 1-expressing fibers 50,53.…”
Section: Introductionmentioning
confidence: 99%
“…This is of interest given that slow-to-fast fiber transitions are reported in human OSAS11,12,48 and that the relative area of fast fatigable fibers is increased in the English bulldog model of OSAS 49. The duration of CIH exposure is a key determinant of the respiratory muscle responses39,50 such that several weeks of exposure increases upper airway muscle fatigue37,4042,44,45 and impairs recovery from fatigue 36,37…”
Section: Introductionmentioning
confidence: 99%
“…An increase in the proportion of fast fatiguable 2B fibres was observed by Pae et al (2005), consistent with observations of decreased muscle endurance (Pae et al, 2005), a finding which resonates with observations of slow-to-fast fibre transitions in OSAS (Series et al, 1995(Series et al, , 1996a, and increased relative area of fast fibres in an upper airway muscle of the English bulldog (Petrof et al, 1994), a model of OSAS. Upper airway muscle dysfunction is dependent on the duration of exposure to CIH, illustrating the cumulative deleterious nature of CIH-related stress in respiratory muscle (Pae et al, 2005;Shortt et al, 2014), which may be NADPH oxidase-dependent . When extended for several weeks of exposure, CIH can also increase upper airway muscle fatigue and delay recovery from fatigue (McGuire et al, 2002a,b).…”
Section: Chronic Intermittent Hypoxia Is a Dominant Feature Of Osas Dmentioning
confidence: 99%
“…CIH increases endoplasmic reticulum stress and apoptotic signalling , with evidence of aberrant sub-cellular structural remodelling (Huang et al, 2012;Zhang et al, 2010), although only modest cellular oxidative stress has been noted in some models . The pivotal role of redox signalling in CIH-induced upper airway dysfunction is revealed by antioxidant intervention studies, which ameliorate or prevent CIH-induced aberrant changes in respiratory muscle (Dunleavy et al, 2008;Skelly et al, 2012a;Shortt et al, 2014).…”
Section: Chronic Intermittent Hypoxia Is a Dominant Feature Of Osas Dmentioning
confidence: 99%